PRO KONTRA SISTEM AKUNTANSI SYARIAH DI INDONESIA TERKAIT KONVERGENSI IFRS DI INDONESIA - ELTHAF ILAHIYAH, MAR'A Elthaf (Jurnal Akuntansi AKUNESA, 2012)
Islamic accounting system is one solution upholding the principles of justice releated to the phenomenon of the conventional accounting system which basics on capitalism. Islamic accounting values postulated to faith and hold fast to the Al-Qur’an and Al-Hadist. But the implementation of syariah in Indonesia, accounting system is pivot on conventional accounting, while the principles of Islamic teachings is a complement to “Islamic” only. PSAK Islamic accounting has not been able to make the parties concerned feel quite statisfied. The problems of applying the syariah based Islamic accounting is nothing completed, Islamic accounting are faced with trouble releated to IFRS.Key words : Islamic accounting system, Conventional accounting system